A 'Brutalizing' War? The USA after the First World War. (January 2015) - Keene, Jennifer
Were US citizens brutalized by the First World War? Mobilization unified the nation, forcing both the willing and unwilling to take a stand in regards to the war and war-induced changes within American society. The spike in the use of violence to achieve political goals during the postwar period coincided with the return of veterans from the battlefield, but veterans did not instigate this period of violence. Rather than brutalization through combat, the 'radicalizing' effect of the war stemmed from how the mobilization process politicized both civilians and soldiers. The effects of war-related politicization resonated into the postwar period in both violent ways (giving the appearance of brutalization) and non-violent ways. Widespread violence in 1919, however, was only one variant of the more general radicalization and politicization US society underwent during the First World War. The non-violent trajectories that developed more fully in the early 1920s were less visible but equally important legacies of wartime mobilization. Over time, politicized veterans within the civil rights movement and veterans organizations quickly opted for nonviolent over violent forms of political expression. The USA thus joined the ranks of the other victor nations where successful veteran reintegration into existing social, economic, and political structures helped to mitigate war-associated violence. The state's embrace of veterans' demands for benefits ultimately gave most returned servicemen a stake in maintaining rather than challenging the existing political system. This did not mean that the effects of wartime politicization evaporated. Instead the two key social justice movements of the twentieth century, the fight for racial equality and the equitable distribution of income, benefited from the injection of politicized veterans into these respective causes.